2006
DOI: 10.1038/sj.onc.1209450
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GCIP in transgenic mice decreases susceptibility to chemical hepatocarcinogenesis

Abstract: Transcription factors with helix-loop-helix (HLH) motif play critical roles in controlling the expression of genes involved in lineage commitment, cell fate determination, proliferation, and tumorigenesis. To examine whether the newly identified HLH protein GCIP/CCNDBP1 modulates cell fate determination and plays a role in hepatocyte growth, proliferation, and hepatocarcinogenesis, we generated transgenic mice with human GCIP gene driven by a liver-specific albumin promoter. We demonstrated that in GCIP transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 61 publications
(67 reference statements)
2
33
0
Order By: Relevance
“…Liver injury causes liver regeneration primarily through hepatocyte division but if hepatocyte division is impaired, liver repair requires the recruitment of hepatic oval cells (Ma et al, 2006). Oval cells mainly express a-fetoprotein but not albumin, and can proliferate and differentiate into both hepatocytes and bile duct cells.…”
Section: Discussionmentioning
confidence: 99%
“…Liver injury causes liver regeneration primarily through hepatocyte division but if hepatocyte division is impaired, liver repair requires the recruitment of hepatic oval cells (Ma et al, 2006). Oval cells mainly express a-fetoprotein but not albumin, and can proliferate and differentiate into both hepatocytes and bile duct cells.…”
Section: Discussionmentioning
confidence: 99%
“…The TNAP-AID mouse model exhibits several characteristics of human HCC, in that the mice develop HCC spontaneously and the HCC tissue expresses a-fetoprotein and that it has the p53 gene mutations, some of which cause the same amino acid replacements as those seen in human tumours. Earlier HCC mouse models include mice with genetic modifications of Lkb1, Mdr2, Aox and Pten genes (Fan et al, 1998;Nakau et al, 2002;Horie et al, 2004;Katzenellenbogen et al, 2006), transgenic mice overexpressing c-myc, transforming growth factor-a, transforming growth factor-b1, HBx of hepatitis B virus and HCV core (Sandgren et al, 1989;Kim et al, 1991;Murakami et al, 1993;Koike et al, 1994Koike et al, , 2002Factor et al, 1997;Riehle et al, 2008) and chemical-or diet-induced HCC (Sell, 2001;Maeda et al, 2005;Ma et al, 2006;Sakurai et al, 2006). In contrast to these models, our TNAP-AID model is unique because it does not arbitrarily target specific oncogenes, tumour suppressors or stability genes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Sonnenberg-Riethmacher et al (2007) reported that lack of Maid (GCIP) promotes the occurrence of HCCs in older mice, suggesting the absence of GCIP can contribute to a higher tumor incidence in the liver. Third, Ma et al (2006) showed that overexpression of GCIP in mouse liver suppressed diethylnitrosamineinduced liver tumors in transgenic mice at an early stage of tumor development. Importantly, their studies suggest that GCIP might be a tumor suppressor protein.…”
Section: Discussionmentioning
confidence: 99%
“…Since GCIP could inhibit the expression of cyclin D1 protein in the cells (Ma et al, 2006), we also examined whether overexpression of P0 could enhance the expression of cyclin D1 protein in the cells. As shown in Figure 4, western blot analysis revealed that the expression level of cyclin D1 increased.…”
Section: P0-overexpressing Cells Exhibit Increased Cyclin D1 Expressimentioning
confidence: 99%